EFFECTS OF NUTRITIONAL STATUS ON PULMONARY IMMUNE FUNCTION AND RESPONSE IN ELDERLY INDIVIDUALS (CIPEEX, 2025)
Objectives: The aging process, as well as caloric-protein malnutrition, is associated with a progressive decline in lung function and a reduction in systemic immune response. However, it is unknown to what extent aging and caloric malnutrition can affect these responses. Method: A randomized clinical trial was conducted at the Evangelical University of Goiás (UniEVANGÉLICA), where 66 elderly individuals (aged 60 to 85 years) were evaluated for lung function, pulmonary immune response through IL-10 measurement in condensed air, peripheral strength through handgrip strength, and respiratory muscle strength through manovacuometry. Results: The results showed that of the 66 elderly individuals evaluated, 44 (67.28%) were classified as hypocaloric, 19 (28.12%) as normocaloric, and 3 (4.68%) as hypercaloric. When comparing the hypocaloric group with the normocaloric group, results show that the hypocaloric group had a reduction in forced vital capacity (FVC, p
Keywords: elderly; resistance training; pulmonary inflammation; cytokines